Application of a body-weight-supporting kite for sprint running - Kratky, S.; Müller, E. (The Journal of Strength and Conditioning Research, 2013)
Improvements in sprint performance at the top level require adaptations concerning force application because ground contact time diminishes with increasing velocity. Applied training methods and devices must provoke appropriate stimuli. A knowledge about positive and negative effects of these stimuli is vital for coaches. The purpose of this study was to determine the angle of attack and lifting and retarding forces of a novel sprint training device that supports the athlete's body weight (BW), thereby decreasing ground contact time during sprints. Three different kite sizes (1.10, 1.75, 2.25 m2) were investigated. A bicycle was used to accelerate the National Aeronautics and Space Administration (NASA) parawings (NPW-120, NPW-150, and NPW-170) on an indoor track to acquire data at velocities between 6.5 and 10.5 m/s. During a 5-m interval of constant speed, the resultant force of the kite was recorded on a portable computer by a load cell. The angle of attack was determined by a high-speed camera, and the mean velocity in the 5-m sector was measured by a laser gauge. Lifting and retarding forces were derived from the resultant force and angle of attack. Quadratic regression equations for lifting and retarding forces, depending on the velocity, were calculated for all 3 NPWs. A clear difference (p < 0.001) depending on the kite size was revealed for lifting and retarding forces. These forces also indicated high correlation coefficients related to velocity (r > 0.98; p < 0.001), whereas the angle of attack remained almost constant across the entire velocity range in all NPWs, yielding a lift-to-drag ratio of 2.35. Because of the kite's small retarding forces, we recommend the application of the NPW during the high-speed phase of sprinting with lifting force probably counteracting adverse effects. By adding a towing system, the retarding force can be fine tuned, erased, or turned into overspeed assistance, thereby emphasizing BW support.